2019
DOI: 10.1109/access.2018.2882074
|View full text |Cite
|
Sign up to set email alerts
|

How to Cache in Mobile Hybrid IoT Networks?

Abstract: Content-centric mobile hybrid Internet-of-Things (IoT) networks consisting of mobile devices and static femto access points (FAPs) are studied, where each device moves according to the random walk mobility model and requests a content object from the library independently at random according to a Zipf popularity distribution. Instead of allowing access to content objects at macro base stations via costly backhaul providing connection to the core network, we consider a more practical scenario where mobile devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Therefore, it reduces the content retrieval time for the IoT devices as it brings the required content near the subscriber by caching it on the nearby nodes [26], [35], [36], [108]- [114]. Other benefits of ICN and in-network caching for IoT networks include improved cache hit ratio, reduced hop count, increased content availability and reliability, reduced network traffic, and reduced energy consumption [102], [103], [106], [115]- [117].…”
Section: A In-network Cachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it reduces the content retrieval time for the IoT devices as it brings the required content near the subscriber by caching it on the nearby nodes [26], [35], [36], [108]- [114]. Other benefits of ICN and in-network caching for IoT networks include improved cache hit ratio, reduced hop count, increased content availability and reliability, reduced network traffic, and reduced energy consumption [102], [103], [106], [115]- [117].…”
Section: A In-network Cachingmentioning
confidence: 99%
“…It was observed that when content popularity is considered during cache decisions, the content transfer time and packet loss ratio can be reduced while increasing the content availability. It was also observed in [117] that in mobile hybrid ICN-IoT, both mobile devices and static femto access points might be equipped with finite-size cache space. Then, an order-optimal cache allocation strategy can be applied to optimize the performance.…”
Section: A In-network Cachingmentioning
confidence: 99%
“…Recently, D2D caching has been actively studied, in order to allow end terminals to cache content files and then to directly serve each other via D2D single-hop or multihop file delivery [5][6][7][8]11,12]. Specifically, the optimal throughput scaling laws for D2D caching networks achievable by single-hop file delivery and multihop file delivery were derived in [5,11,12]. Analytical modeling for traffic dynamics has been studied in [6] to investigate packet loss rates for cache-enabled networks.…”
Section: Related Workmentioning
confidence: 99%
“…The content placement is a process in which the user's requested content is cached in the caching nodes along the forwarding path. It has a significant role to improve the overall network performance [7] [8].…”
Section: Introductionmentioning
confidence: 99%